Procedural Content Generation for Location-based Games - Ana Margarida Cardoso Carraca (2014)
Location-based games are games where the physical position of the player has influence on thegameplay. Most of these games are currently developed with a specific location in mind, so asto provide the user with a more immersive experience. Thus, procedural content generation haspotential to be of great value to this type of games, as they can be extended to arbitrary locationsin a less labor-intensive fashion.The main goal of this dissertation is to create a tool that is able to generate a model of thecurrent location based on geographical data. Non-player characters containing knowledge of thelocation are used to interact with the player. Procedural Content Generation techniques will beused to generate the components, and a possible impact of the use of this tool for tourism purposeswill be studied.